Anaerobic treatment of lactic waste and goat manure (2011)
Anaerobic digestion was carried out to obtain biogas from lactic waste in combination with goat manure. Waste from lactic products such as cream, cheese and whey was mixed with goat manure using three formulations; the quantity of waste from cream and cheese was maintained, and only the quantity of manure and whey was varied. Methanogenic bacteria obtained from predigestion of goat manure were used as inoculants. Temperature was 35ºC and pH 7.0.Biogas methane percentage was determined by gas chromatography. The results showed that the highest methane concentration obtained was 82% with formulation III.